Cardiac involvement in inflammatory myopathies and inherited muscle diseases. Issue 6 (November 2020) - Lilleker, James B.; Roberts, Mark; Diederichsen, Louise
Abstract : Purpose of review: To examine recent developments relating to cardiac involvement in the adult idiopathic inflammatory myopathies (IIM) and those inherited muscle diseases which may present in adulthood and mimic IIM. Recent findings: Cardiac involvement is a common feature of IIM and inherited muscle diseases. Frequency according to disease subtype varies, with serotype having particular influence in IIM, and genotype in the inherited muscle diseases. Innovative techniques for examining cardiac function have been investigated further, including speckle-tracking echocardiography and cardiac magnetic resonance tomography. The present work has highlighted a likely underestimate of the burden of cardiac disease to date. The complex relationship between IIM, atherosclerosis, and traditional cardiovascular risk factors has been further elucidated. Consensus recommendations for managing patients with inherited muscle diseases and prominent cardiac involvement have been recently published. In addition to supportive care, disease modifying treatments are increasingly becoming available for inherited muscle diseases which may also improve cardiac outcomes. Summary: Cardiac involvement is associated with significant morbidity and mortality. We suggest having a low threshold for considering the possibility of cardiac involvement in all patients with muscle disease.